Studi kasus : Pemanfaatan Game Online untuk Peningkatan Motivasi Belajar Peserta Didik di SDN Alalak Selatan 2 - Diah Fitriani; Ahmad Suriansyah; Arta Mulya Budi Harsono; Dessy Dwitalia Sari; Mubarok, Mubarok (GLOBAL SCIENTS PUBLISHER, 2024)
This research aims to analyze and describe online games as an alternative for increasing students' learning motivation in elementary school. Technological advances in the world of education certainly have a big influence, starting from learning media to strategies and learning methods that are different from previous times. The method applied in this research is a qualitative approach with case studies. Data was collected through interviews, observation and documentation at SDN Alalak Selatan 2. The research subjects consisted of Class V homeroom teachers and class V students. Data collection was carried out through observation, interviews and documentation. Observations are carried out to observe. student behavior and responses when using online games in learning. The researcher determines the class and students who will be observed, then creates an observation schedule that includes several learning sessions. During observations, researchers recorded students' interactions with online games, including their level of engagement and responses to tasks given through the game. Changes in learning motivation, such as increased participation, enthusiasm, and persistence in completing assignments, were also noted. Apart from observations, interviews were conducted to obtain in-depth views from students and teachers regarding the use of online games in learning. Interviews were conducted with participants who had been observed as well as several teachers involved in the learning process. This research concludes that the use of online games in education has great potential to increase students' learning motivation.